Social-Psychological Aspects of Prevention from Cyber Attacks in Adolescents (Zien Journal of Social Sciences and Humanities, 2022)
This article highlights the psychological interpretation of cyberattack prevention. Also, the use of prevention from cyber attacks as a research subject of psychology and as a criterion determining the main essence in psychological research is analyzed.